THE INFLUENCE OF CONTINUING PROFESSIONAL EDUCATION, AUDITOR ASSIGNMENT PERIOD, INDUSTRY SPECIALIZATION ON COMPLIANCE WITH AUDIT STANDARDS, IMPLEMENTATION OF DATA ANALYTIC TECHNIQUES, AND QUALITY OF AUDIT RESULTS IN AUDITORS OF NON-BIG 4 PUBLIC ACCOUNTING - Septian, Michael Revelin Ervan; Ratnawati, Tri (Universitas 17 Agustus 1945 Surabaya, 2023)
The aim of this research is to examine and analyze the influence of Continuing Professional Education, Auditor Assignment Period, Industry Specialization on Compliance with Audit Standards, Implementation of Data Analytic Techniques , and Quality of Audit Results. This research took respondents from auditors from non- big 4 public accounting firms in the city of Surabaya from junior auditor to partner level , with a total sample of 60 people. Hypothesis testing in this research uses analysis with the SmartPLS application by testing the outer model and inner model. The research results show that continuing professional education has a significant effect on compliance with audit standards, the auditor's assignment period has a significant effect on the implementation of data analytic techniques , industry specialization has a significant effect on the quality of audit results, implementation of data analytic techniques has a significant effect on the quality of audit results.